Rendimento do feijão-fava (Phaseolus lunatus l.) em função da adubação organomineral - Alves, Adriana Ursulino (2006)
It was aimed at to evaluate the productivity of the bean-broad bean, "Raio-de-Sol" variety, in function of doses of bovine manure in the presence and absence of NPK. For so much, an experiment was accomplished, in the period of September of 2004 to May of 2005, in typical Quartzpsament soil, in the Federal University of Paraíba, in Areia city. It was used the experimental design of randomized blocks, in factorial outline 6 x 2, with four repetitions, being the constituted experimental portion of 40 plants. They were appraised the length of beans, the number and the production of beans and of grains, for plant, the productivity of beans and of green and dry grains and the tenors of NPK in the tissue foliar. The maximum length of beans, 8,7 cm, it happened being used 19,5 and 17,5 t ha-1 of bovine manure, in the presence and in the absence of NPK, respectively. The levels of 22,6 and 21,7 t ha-1 of bovine manure, respectively, they were responsible for the maximum numbers of 41 and 38 beans by plant in the presence and in the absence of NPK. The maximum productions of beans and of grains by plant of 125,9 and 35,3 g, respectively, they were obtained with 26,6 t ha-1 of bovine manure, in the presence of NPK, while in your absence, the maximum production of beans of 111,9 g was reached with 21,4 t ha-1 of bovine manure, and the medium production of 19,2g of grains, for plant, in function of the levels of bovine manure. The levels of 21,4 and 23,0 t ha-1 of bovine manure they were responsible for the maximum productivities of beans (12,6 and 11,2 t ha-1), in the presence and in the absence of NPK, respectively, while the levels of 21,3 and 22,9 t ha-1 of bovine manure they provided maximum productivities of green grains of 11,1 and 9,9 t ha-1, respectively, in the presence and in the absence of NPK. The level of 26,6 t ha-1 of bovine manure it was responsible for the maximum productivity of 3,5 t ha-1 of dry grains, in the presence of NPK. In the absence of NPK, it was obtained the medium productivity of 2,0 t ha-1, in function of the levels of bovine manure. The levels of 17,0 and 18,6 t ha-1 of bovine manure they provided maximum economical efficiencies for the productivity of beans, with foreseen revenues of 2,88 and 3,36 t ha-1, respectively, in the presence and in the absence of NPK. For the productivity of dry grains, the maximum economical efficiency was obtained with 23,0 t ha-1 of bovine manure, with revenue of 2,12 t ha-1. The levels of bovine manure just influenced the tenor of K in the presence of NPK, while in your absence it was observed it only differentiates in the tenor of N.